Clinical evaluation of fully automated molecular diagnostic system “Simprova” for influenza virus, respiratory syncytial virus, and human metapneumovirus - Takayama, Ikuyo; Semba, Shohei; Yokono, Kota; Saito, Shinji; Nakauchi, Mina; Kubo, Hideyuki; Kaida, Atsushi; Shiomi, Masashi; Terada, Akihiro; Murakami, Kiyotaka; Kaji, Katsushi; Kiya, Keiichi; et al. (Scientific reports, 2020)
Influenza virus, respiratory syncytial virus, and human metapneumovirus commonly cause acute upper and lower respiratory tract infections, especially in children and the elderly. Although rapid antigen detection tests for detecting these infections have been introduced recently, these are less sensitive than nucleic acid amplification tests. More recently, highly sensitive point-of-care testings (POCTs) have been developed based on nucleic acid amplification tests, which are easy to use in clinical settings. In this study, loop-mediated isothermal amplification (LAMP)-based POCT “Simprova” to detect influenza A and B viruses, respiratory syncytial virus, and human metapneumovirus was developed. Simprova system is fully automated and does not require skilled personnel. In addition, positive results can be achieved faster than with PCR. In this study, the accuracy of the POCT was retrospectively analyzed using 241 frozen stocked specimens. Additionally, the usability of the Simprova at clinical sites was assessed in a prospective clinical study using 380 clinical specimens and compared to those of real-time PCR and rapid antigen detection test. The novel LAMP-based POCT demonstrated high sensitivity and specificity in characterizing clinical specimens from patients with influenza-like illnesses. The Simprova is a powerful tool for early diagnosis of respiratory viral infections in point-of-care settings.